Evaluation of novel approaches to software engineering 5th international conference, ENASE 2010, Athens, Greece, July 22-24, 2010, revised selected papers - ENASE (Conference) 2010 Athens, Greece); Maciaszek, Leszek A.; Loucopoulos, Pericles; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This book contains a collection of thoroughly refereed papers presented at the 5th International Conference on Evaluation of Novel Approaches to Software Engineering, ENASE 2010, held in Athens, Greece, in July 2010. The 19 revised and extended full papers were carefully selected from 70 submissions. They cover a wide range of topics, such as quality and metrics; service and Web engineering; process engineering; patterns, reuse and open source; process improvement; aspect-oriented engineering; and requirements engineering.
Electronic reproduction.
Keywords: Software engineering -- Congresses; Electronic books; Management of Computing and Information Systems